Mind chi : re-wire your brain in 8 minutes a day : strategies for success in business and life - Israel, Richard, 1942- (Capstone Pub., 2010)
"Mind Chi is a powerful synthesis of thought and action based on the most recent research into how the brain works. By following the simple, daily exercises in this book, you will raise your mental performance to a level you never thought possible"--Resource description page.